Expression of perforin, granzyme A and Fas ligand mRNA in caecal tissues upon Eimeria tenella infection of naïve and immune chickens - Smith, A; Wattrang, E; Magnusson, S; Näslund, K; Thebo, P; Hagström, Å; Lundén, A (Wiley, 2016)
Cytotoxic cells of the immune system may kill infected or transformed host cells via the perforin/granzyme or the Fas ligand (FasL) pathways. The purpose of this study was to determine mRNA expression of perforin, granzyme A and FasL in Eimeria tenella infected tissues at primary infection and infection of immune chickens as an indirect measure of cytotoxic cell activity. Chickens were rendered immune by repeated E. tenella infections, which was manifested as an absence of clinical signs or pathological lesions and significantly reduced oocyst production upon challenge infection. During primary E. tenella infection perforin, granzyme A and FasL mRNA expression in caecal tissue was significantly increased at 10 days after infection, compared to uninfected birds. In contrast at infection of immune birds perforin and granzyme A mRNA expression in caecal tissue was significantly increased during the early stages of E. tenella challenge infection, days 1-4, which coincided with a substantial reduction of parasite replication in these birds. These results indicate the activation of cytotoxic pathways in immune birds and support a role for cytotoxic T-cells in the protection against Eimeria infections.